Radiologic Evaluation of Lower Leg, Ankle, and Foot Fracture Fixation Hardware - Mar, Winnie A.; Schilling, J. Hank; Lomasney, Laurie; Chen, Eric; Taljanovic, Mihra S.; Lowe, Jason (Seminars in Musculoskeletal Radiology, 2019)
Radiologists should be familiar with basic principles of fracture fixation and the normal imaging appearances of implant constructs and their complications. The surgeon's selection of external fixation, intramedullary nail fixation, open reduction and internal fixation, or some combination depends on patient factors, fracture configuration, injury to the soft tissue envelope, and surgeon experience. Complications including loss of fixation with resultant malalignment, nonunion, infection, and posttraumatic osteoarthritis present additional challenges for the surgeon as well as the radiologist. This article reviews the rationale behind fracture fixation in fractures of the lower leg, ankle, and foot. Examples of postoperative complications are also reviewed.
Keywords: fracture fixation; lower leg; ankle; foot